Oxidants, antioxidants and mitochondrial function in non-proliferative diabetic retinopathy - Rodríguez-Carrizalez, Adolfo Daniel (J Diabetes, 2014)
BACKGROUND: Diabetic retinopathy (DR) is a preventable cause of visual disability. The aims of the present study were to investigate levels and behavior oxidative stress markers and mitochondrial function in non-proliferative DR (NPDR) and to establish the correlation between the severity of NPDR and markers of oxidative stress and mitochondrial function. METHODS: In a transverse analysis, type 2 diabetes mellitus (T2DM) patients with mild, moderate and severe non-proliferative DR (NPDR) were evaluated for markers of oxidative stress (i.e. products of lipid peroxidation (LPO) and nitric oxide (NO) catabolites) and antioxidant activity (i.e. total antioxidant capacity (TAC), catalase, and glutathione peroxidase (GPx) activity of erythrocytes). Mitochondrial function was also determined as the fluidity of the submitochondrial particles of platelets and the hydrolytic activity of F(0)/F(1)-ATPase. RESULTS: Levels of LPO and NO were significantly increased in T2DM patients with severe NPDR (3.19 ± 0.05 μmol/mL and 45.62 ± 1.27 pmol/mL, respectively; P < 0.007 and P < 0.0001 vs levels in health volunteers, respectively), suggesting the presence of oxidative stress. TAC had significant decrease levels with minimum peak in severe retinopathy with 7.98 ± 0.48 mEq/mL (P < 0.0001). In contrast with TAC, erythrocyte catalase and GPx activity was increased in patients with severe NPDR (139.4 ± 4.4 and 117.13 ± 14.84 U/mg, respectively; P < 0.0001 vs healthy volunteers for both), suggesting an imbalance between oxidants and antioxidants. The fluidity of membrane submitochondrial particles decreased significantly in T2DM patients with mild, moderate, or severe NPDR compared with that in healthy volunteers (P < 0.0001 for all). Furthermore, there was a significant increase in the hydrolytic activity of the F(0)/F(1)-ATPase in T2DM patients with mild NPDR (265.07 ± 29.55 nmol/PO(4); P < 0.0001 vs healthy volunteers), suggesting increased catabolism. CONCLUSIONS: Patients with NPDR exhibit oxidative deregulation with decreased membrane fluidity of submitochondrial particles and increased systemic catabolism (mitochondrial dysfunction) with the potential for generalized systemic damage in T2DM.